On numerical solution of the time-fractional diffusion-wave equation with the fictitious time integration method - Hashemi, M. S.; İnç, Mustafa; Parto-Haghighi, M.; Bayram, Mustafa (Springer Heidelberg, 2019)
.In this work we offer a robust numerical algorithm based on the Lie group to solve the time-fractional diffusion-wave (TFDW) equation. Firstly, we use a fictitious time variable xi to convert the related variable u(x, t) into a new space with one extra dimension. Then by using a composition of the group preserving scheme (GPS) and a semi-discretization of new variable, we approximate the solutions of the problem. Finally, various numerical experiments are performed to illustrate the power and accuracy of the given method.
Keywords: Lie Symmetry Analysis; Differential-Equations; Fundamental-Solutions; Boussinesq; Solve